Understanding the effects of prematurity on clinical manifestations of neonatal abstinence syndrome: A narrative literature review. Issue 6 (December 2020) - Song, Grace; Pak, Victoria M.
Abstract: Introduction: Neonatal abstinence syndrome is a collection of postnatal withdrawal symptoms caused by in-utero exposure to opioids. Despite the high association with prematurity, there is a lack of research informing proper identification of neonatal abstinence syndrome in preterm newborns. Objective: To delineate contrast in clinical manifestations of neonatal abstinence syndrome between preterm and full-term newborns, and to explain how common morbidities of prematurity may be responsible for the identified differences. Methods: A literature search was undertaken in PubMed, Google Scholar, and PsychInfo. Results: Five research studies, discussing neonatal abstinence syndrome symptomatology related to gestational age or morbidities of prematurity, were reviewed. Conclusion: Preterm newborns with neonatal abstinence syndrome present in ways that are distinct from full-term newborns and untraceable by diagnostic assessment tool currently available. A better understanding of pathophysiology of neonatal abstinence syndrome in the context of prematurity is necessary in order to improve assessment and intervention outcomes.